The Influence of Internal Control of Raw Material Inventory and Production Process Planning on the Smoothness of the Production Process in the Production Department of PT. Hogy Indonesia Cibitung - Sabarudin, Laode (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
The purpose of this research is to find out the influence of internal control of raw material inventory and production process planning on the smoothness of the production process in the production department of PT. Hogy Indonesia Cibitung. This research applies a quantitative-causality approach. The measurement of research variables uses the Likert Scale for each statement developed from each indicator variable. The population in this study consists of employees in the Over All Drape department. The sample used in this research consisted of 56 respondents, and the sampling technique was non-probability sampling. Data analysis techniques applied in this research were statistical techniques such as validity and reliability tests for the questionnaire and multiple linear regression analysis with f-test and t-test for hypothesis testing. The study found that internal control of raw material inventory and production process planning have a positive influence on the smoothness of the production process in the Over All Drape department. Internal control of raw material inventory and production process planning together simultaneously have a positive influence on the smoothness of the production process in the Over All Drape department.